2021
DOI: 10.3389/fpubh.2021.675380
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Internet Use Was Associated With Psychological Problems Among University Students During COVID-19 Outbreak in China

Abstract: Background: As the coronavirus disease 2019 (COVID-19) pandemic progressed globally, school closures and home quarantine may cause an increase in problematic Internet use among students in universities. Such a traumatic stress event may also contribute to the development of posttraumatic stress disorder (PTSD), depressive, and anxiety symptoms. This study aimed to evaluate the prevalence of PTSD, depressive, and anxiety symptoms as well as the predictive role of problematic Internet use in the above-mentioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…Moreover, a statistically significant mediatory role of COVID-19-related depressive symptomatology was reported in mediating the interaction between the IAT and IGDS. These findings may underline how current COVID-19-induced depressive symptomatology may act as a mediatory trigger in the development and maintenance of behavioral addictions, as already demonstrated in previous studies [37,38,[71][72][73]. Moreover, our findings reported a prevalence which is relatively lower than that reported in the early COVID-19 phases in Italy, with an increasing trend for PIU and IA from phase II towards phase III of the COVID-19 outbreak.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, a statistically significant mediatory role of COVID-19-related depressive symptomatology was reported in mediating the interaction between the IAT and IGDS. These findings may underline how current COVID-19-induced depressive symptomatology may act as a mediatory trigger in the development and maintenance of behavioral addictions, as already demonstrated in previous studies [37,38,[71][72][73]. Moreover, our findings reported a prevalence which is relatively lower than that reported in the early COVID-19 phases in Italy, with an increasing trend for PIU and IA from phase II towards phase III of the COVID-19 outbreak.…”
Section: Discussionsupporting
confidence: 86%
“…In fact, the fear resulting from the COVID-19 situation and the lockdown-related consequences, together with high levels of stress and anxiety, have been mounting [28,29]. A number of factors, including the greater time spent at home due to lockdown, alone or with family members, with high levels of uncertainty and worries regarding the future, financial insecurity and fear related to health consequences, not only contributed to increase stress, anxiety and depression, but also to worsen general psychological wellbeing [28,[30][31][32][33][34][35][36][37][38][39][40]. This situation may reinforce behaviors such as PIU, problematic video gaming disorder (PVGD), problematic TV series watching, PSMU, watching online pornography or surfing the internet [15,16,18,20,21,41].…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings can be found in previous studies from other countries ( 28 , 29 , 31 , 32 , 98 ). In this context, problematic Internet use may be a predictor in screening high-risk students for mental health problems ( 30 ). Jiang et al ( 27 ) also revealed that internet addiction was directly related to college students' depression and indirectly predicted students' depression via the mediator of social support and sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, respondents could select one of the following answers for each of the 10 items: never-−0, almost never-−1, sometimes-−2, fairly often-−3, very often-−4. The ranges of the total PSS-10 score indicated: low stress (0-13), moderate stress (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), and high stress (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Accordingly, the higher the total score, the more severe the psychological distress.…”
Section: Methodsmentioning
confidence: 99%
“…When a problem is identified, increased attention is focused not only on the time spent online, but especially on consequences such as loss of control, unsuccessful quit attempts, or disrupted relationships with family and friends ( 26 ). In addition, evidence clearly shows that problematic internet use is a significant predictor of depression, anxiety, and stress in young people ( 27 , 28 ). On the other hand, there are also findings indicating that the presence of common mental disorders may explain problematic internet use ( 16 ).…”
Section: Introductionmentioning
confidence: 99%